Implementing Time Driven Activity Based Budgeting (TDABB) In Educational Institutions: A Case Study - Kadhim, Hatem Karim; Kadhim, Mithal Kareem (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims to encourage the educational sector to use modern budget entries as a budget approach on the basis of TDABB in order to provide more accurate information to budget users that it provides as well as tight control and increase the effectiveness of the planning process in the future. It also aims to motivate educational institutions, including the University of Babylon, to use contemporary cost management approaches such as the TDABB approach, which contributes to improving educational services and reducing their costs. The study adopts the case study method in one of the educational institutions in Iraq, which is the University of Babylon. The results show that the preparation of the operational budget in service institutions in general and educational institutions in particular differs from that in industrial institutions due to the difference in the characteristics of educational services and the nature of spending on them from the properties of products and elements of industrial costs. Educational services are produced and delivered at the same time. The goal of preparing the budget on the basis of TDABB is to prepare the resources that are required to produce and provide the educational service. Most universities have an inflexible organizational structure to the point where they cannot make the necessary adjustments when implementing the budget. The information provided by the cost approach can also be used on the basis of TDABB in preparing the operational budget in educational institutions.